From Norvelt to Nowhere : Norvelt Series #2 - Gantos, Jack (New York : Farrar, Straus and Giroux, 2013)
After an explosion, a new crime by an old murderer, and the sad passing of the founder of Norvelt, Pennsylvania, twelve-year-old Jack accompanies his slightly mental elderly mentor, Miss Volker, on a cross-country run as she pursues the oddest of outlaws.
Sequel to: Dead end in Norvelt
Keywords: Friendship -- Fiction; Old age -- Fiction; Mystery and detective stories; Norvelt (Pa.) -- History -- 20th century -- Fiction; Humorous fiction